Association of JNC-8 and SPRINT Systolic Blood Pressure Levels With Cognitive Function and Related Racial Disparity - Hajjar, Ihab (JAMA Neurol, 2017)
IMPORTANCE: The Eighth Joint National Committee (JNC-8) recommended treating systolic blood pressure (SBP) to a target below 150 mm Hg in older adults, whereas data from the Systolic Blood Pressure Intervention Trial (SPRINT) suggested that a SBP level of lower than 120 mm Hg decreases cardiovascular event rates. Target SBP guidelines have not addressed the potential that black patients may have greater morbidity and mortality from hypertension, especially with regard to cognitive outcomes. The association of these discordant SBP targets with cognition and differences by race have not been systematically evaluated in the same population. OBJECTIVES: To assess the long-term outcomes of the various recommended SBP levels and to determine if racial differences exist based on long-term cognitive trajectories. DESIGN, SETTING, AND PARTICIPANTS: A total of 1657 cognitively intact older adults receiving treatment for hypertension were studied from 1997 to 2007 in the Health Aging and Body Composition study. Data analysis was conducted from October 1, 2016, to January 1, 2017. MAIN OUTCOMES AND MEASURES: Cognition was assessed using the Modified Mini-Mental State Examination (3MSE) 4 times and the Digit Symbol Substitution Test (DSST) 5 times. At each visit, participants were classified as having an SBP level of 120 mm Hg or lower, 121 to 139 mm Hg, 140 to 149 mm Hg, or 150 mm Hg or higher based on the mean SBP level of 2 seated readings. Mixed models assessed the association of SBP levels with 10-year cognitive trajectories. The impact of race was tested using a race interaction term. RESULTS: During the 10-year study period, among the 1657 individuals (908 women and 784 black patients; mean [SE] age, 73.7 [0.1] years), there was a differential decrease in 3MSE and DSST scores by the SBP levels, with the greatest decrease in the group with SBP levels of 150 mm Hg or higher (adjusted decrease was 3.7 for 3MSE and 6.2 for DSST) and the lowest decrease in the group with SBP levels of 120 mm Hg or lower (adjusted decrease was 3.0 for 3MSE and 5.0 for DSST) (P < .001 for both). Compared with white patients, black patients had a greater difference between the higher and lower SBP levels in the decrease in cognition; adjusted differences between the group with SBP levels of 150 mm Hg or higher and the group with SBP levels of 120 mm Hg or lower were –0.05 in white patients and –0.08 in black patients for 3MSE (P = .03) and –0.07 in white patients and –0.13 in black patients for DSST (P = .05). CONCLUSIONS AND RELEVANCE: For patients 70 years of age or older receiving treatment for hypertension, a SPRINT SBP level of 120 mm Hg or lower was not associated with worsening cognitive outcome and may be superior to the JNC-8 target for cognition. Lower SBP treatment levels may result in improved cognition in black patients.